2008
DOI: 10.1597/07-087.1
|View full text |Cite
|
Sign up to set email alerts
|

TGFA/TAQ I Polymorphism in Nonsyndromic Cleft Lip and Palate Patients from Rio Grande Do Sul, Brazil

Abstract: Mutations in TGFA gene have no association with nonsyndromic cleft lip and palate in the sample from Rio Grande do Sul. Therefore, based on this study, it is not possible to determine the role played by TGFA in the expression of cleft lip and palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
4
1
1
Order By: Relevance
“…However, the findings of this meta‐analysis are contrary to our study and the studies by Ehlers Bertoja et al () in a Brazilian population, and Kim et al () in a Korean population (Kim et al, ). This may be due to genetic differences in different populations.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the findings of this meta‐analysis are contrary to our study and the studies by Ehlers Bertoja et al () in a Brazilian population, and Kim et al () in a Korean population (Kim et al, ). This may be due to genetic differences in different populations.…”
Section: Discussioncontrasting
confidence: 99%
“…In the second phase, the full‐text review was then conducted on the 71 first‐phase selected citations, which lead to the exclusion of 22 studies. In the end of the two phases, 49 studies fulfilled the inclusion criteria (Antunes et al, ; Araújo et al, ; Araujo et al, ; Bagordakis et al, ; Bezerra et al, ; Brandalize et al, ; Brito, Bassi, & Masotti, ; Brito et al, ; Bufalino et al, ; Cardoso et al, ; Choi et al, ; da Silva, Ribeiro, Cooper, Marazita, & Moretti‐Ferreira, ; de Aguiar et al, ; de Aquino et al, a,b; de Souza et al, ; do Rego Borges et al, ; Ehlers Bertoja, Sampaio Alho, De França, Menegotto, & Miriam Robinson, ; Falagan‐Lotsch et al, ; Filézio et al, ; Fontoura, Silva, Granjeiro, & Letra, ; Gaspar et al, ; Jehee et al, ; Küchler et al, ; Letra, Menezes, Granjeiro, & Vieira, ; Letra, Silva, & Menezes, ; Letra et al, a,b; Machado et al, a,b, ; Menezes, Letra, Ruff, Granjeiro, & Vieira, ; Menezes et al, ; Messetti et al, ; Paranaíba et al, ; Passos‐Bueno et al, ; Sabóia et al, ; Souza, Kowalski, Collares, & Félix, ; Souza, Kowalski, Vanz, Giugliani, & Félix, ; Waltrick‐Zambuzzi et al, ; Zucchero et al, ), but only 11 articles were used in the meta‐analysis (Antunes et al, ; Araújo et al, ; Bagordakis et al, ; Brito et al, ; de Aguiar et al, ; do Rego Borges et al, ; Fontoura et al, ; Gaspar et al, ; Paranaíba et al, ;).…”
Section: Resultsmentioning
confidence: 99%
“…Case-control and case-parent triad studies in humans have reported conflicting results. Although several etiological studies have insisted that NSCLP is associated with allelic variations of TGFA (Ardinger et al, 1989; Shiang et al, 1993; Beaty et al, 2006), others have not observed such an association (Stoll et al, 1992; Lidral et al, 1997; Rahman et al, 2008; Ehlers Bertoja et al, 2008; Zhu et al, 2010).…”
mentioning
confidence: 99%